Network analytics for drug repurposing in COVID-19 - Siminea Nicoleta; Popescu Victor; Sanchez Martin Jose Angel; Florea Daniela; Gavril Georgiana; Gheorghe Ana-Maria; Iţcuş Corina; Kanhaiya Krishna; Pacioglu Octavian; Popa Laura Iona; Trandafir Romica; Tusa Maria Iris; et al. (Oxford University Press, 2022)
To better understand the potential of drug repurposing in COVID-19, we analyzed control strategies over essential host factors for SARS-CoV-2 infection. We constructed comprehensive directed protein–protein interaction (PPI) networks integrating the top-ranked host factors, the drug target proteins and directed PPI data. We analyzed the networks to identify drug targets and combinations thereof that offer efficient control over the host factors. We validated our findings against clinical studies data and bioinformatics studies. Our method offers a new insight into the molecular details of the disease and into potentially new therapy targets for it. Our approach for drug repurposing is significant beyond COVID-19 and may be applied also to other diseases.